(untitled) (Analele Universității București. Limba și literatură română, 2025)
The paper investigates a special use of diminutive affixes in Romanian. In this use, when attached to mass nouns of the type unt ‘butter’, carne ‘meat’, pască ‘Easter cake’, diminutives yield countable nouns of the type untulețe / ‘butter.DIM.PL’ / ‘packets of butter’, cărnițe / ‘meat.DIM.PL’ / ‘steaks’, păscuțe / ‘Easter cake.DIM.PL’ / ‘pieces of Easter cake’. These countable nouns unambiguously refer to units of stuff, as opposed to kinds of stuff. Following in essence De Belder (2008, 2011), the paper proposes that, in contexts where the count-unit reading arises as a result of diminutive affixation, the respective affixes head their own projection SizeP. In all other cases of diminutive affixation, diminutive affixes are specifiers of a ClassP projection (Fábregas 2013).